Igreja católica, assistência social e caridade: Aproximações e divergências - da Silva, Claudia Neves [UNESP] (FapUNIFESP (SciELO), 2006)
This article is the result of a research study concluded in 2003, which aimed at investigating how the conception of Law is expressed in the actions of the so-called social pastoral commissions of the Catholic Church in Londrina, Brazil. By observing that the conception of charity and that of social rights walk side-bi-side within the Catholic Church, a question emerged: how is the conception of social right expressed in the actions of social pastoral commissions? Charity is preached as a Christian duty, as an action expressed in the experience of solidarity towards others who are in a situation that prevents them from having minimal living conditions. At least at discourse level, the actions developed are not limited to provide basic goods, clothes or medicine. We realized that those who act in social pastoral commissions, driven by values such as love to fellow human beings and solidarity, have not lost sight of the idea of social right - on the contrary, they have been reinforcing it. © 2006 Programa de Pós-Graduação em Sociologia - UFRGS.
The Catholic Church, social assistance, and charity: Approximations and disagreements
Keywords: Catholic church; Charity; Social pastoral commissions; Social problems; Social rights